MENINGKATKAN KETERAMPILAN MEMBUAT BROS JILBAB BERBENTUK CAPUNG MELALUI METODA LATIHAN PADA ANAK TUNAGRAHITA RINGAN - Neli Yanti (Universitas Negeri Padang, 2014)
This study on the back by the problems that appear in the field, the Son of Light Tunagrahita fourth grade in Bukittinggi Ganting SDLB Mangosteen is experiencing problems in skill subjects aimed to determine the increase in children's learning outcomes made ​​Dragonfly Shaped Hijab Brooch skills using Exercise Method. This type of research is action research (Classroom action research), while the subject of this study is the Son of Light Tunagrahita in Class IV SDLB Mangosteen Ganting experiencing problems in Bukittinggi making skills Shaped Hijab dragonfly brooch with the initials S, and P. Based on action given and the results of data analysis showed that: the results of the initial test (assessment) S gain value (26%), and P gain value (32%). Cycle I obtained the highest value of S is (58%), and P (62%). While the second cycle where S gained increased increased (85% , and P (88%). It can be concluded that the method of exercise can improve skills make dragonfly brooch shaped hijabs for mild mental retardation children, it is recommended to teachers in order to implement training methods to improve other skills.